2004
DOI: 10.1667/rr3108
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Treatment Decreases Bone Cancer Pain, Osteolysis and Tumor Size

Abstract: Radiotherapy is the cornerstone of palliative treatment for primary bone cancer in animals and metastatic bone cancer in humans. However, the mechanism(s) responsible for pain relief after irradiation is unknown. To identify the mechanism through which radiation treatment decreases bone cancer pain, the effect of radiation on mice with painful bone cancer was studied. Analysis of the effects of a 20-Gy treatment on localized sites of painful bone cancers was performed through assessments of animal behavior, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 16 publications
0
35
1
Order By: Relevance
“…It is produced by cytokines released from tumour mass in low pH tumour-environment. These cytokines stimulate osteoklasts to osteolysis, and afferent nerve fibers [6,7,12]. This type of pain may be successfully treated with anti-inflammatory drugs.…”
Section: Clinical Presentation and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is produced by cytokines released from tumour mass in low pH tumour-environment. These cytokines stimulate osteoklasts to osteolysis, and afferent nerve fibers [6,7,12]. This type of pain may be successfully treated with anti-inflammatory drugs.…”
Section: Clinical Presentation and Imagingmentioning
confidence: 99%
“…It is not known, how local irradiation decreases cancer-induced pain. Some reports suggested that radiation decreased viable tumour mass, and secondary reduced amount of cytokines and growth factors which activated osteoclasts in tumour-bone microenvironment [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…176 When sarcoma cells (10 5 in 20 μl) were implanted into mouse femurs to examine the effects of 20-Gy and 30-Gy radiation as a means to control cancer pain, these radiation therapies effectively decreased cancer-induced osteolysis, reduced tumor size by 75%, and decreased bone cancerrelated pain. [57][58][59] Radiation therapy also successfully controlled pain and skeletal fractures associated with femoral implantation of 4T1 breast carcinoma cells into mice. 59 These studies demonstrated that radiation therapy effectively decreased cancer-induced pain by direct effects on tumor cells.…”
Section: Models Of Cancer Painmentioning
confidence: 99%
“…In rats, because of the large bone size, it is possible to inject tumor cells percutaneously into the tibia without performing a knee stifle [Medhurst et al, 2002]. With mice, because of diminutive bone size, tumor cells are injected into the humerus or femur after a surgical knee stifle [Wacnik et al, 2003;Goblirsch et al, 2004]. Direct, local intramedullary injection of tumor cells is advantageous over systemic intravenous or intracardiac administration because the skeletal site where the tumor develops is known, allowing for analysis of corresponding behavioral and neuroanatomic segments.…”
Section: Animal Models Of Bone Cancer Painmentioning
confidence: 99%
“…More recently, Goblirsch et al has suggested that reduced tumor burden and reduced osteolysis are the principal contributors through which radiation improves cancerinduced bone pain (Fig. 3) [Goblirsch et al, 2004].…”
Section: Therapies For Cancer-induced Bone Painmentioning
confidence: 99%